Decolonizing Emotional Scaffolding in Lebanese Ma‘āhid: Hermeneutics of Parental Reinforcement - Badawi, Habib (Interdisciplinary Journal of Social Sciences, 2026)
Parental emotional engagement in Lebanese Islamic boarding schools (ma’ahid) has been persistently mischaracterized in prior scholarship through culturally inappropriate terminology, obscuring the psychological and pedagogical mechanisms that underpin parent-child relationships within Beirut’s Sunni educational institutions. Existing research has largely applied Western-centric motivational frameworks without accounting for the collectivistic, honor-based, and religiously grounded structures that define these contexts. Objective: This study reconceptualizes parental emotional reinforcement within culturally appropriate theoretical frameworks by integrating Self-Determination Theory (SDT), Ricoeurian hermeneutics, and culturally responsive pedagogy, and identifies the primary mechanisms through which such reinforcement operates within Lebanese ma’ahid. Method: A qualitative hermeneutic-phenomenological design (Van Manen, 2016) was employed across three schools in Sunni-dominated districts of Beirut (Tariq al-Jdideh and Mazraa), involving 30 students (ages 13–18) and 40 parents. Data were collected through structured observations, systematic document analysis of parental letters and institutional communications, and digital ethnography of school-approved messaging platforms, then analyzed using Ricoeur’s three-level hermeneutic triad framework. Results: Parental emotional support operates through three primary mechanisms: (1) verbal affirmation anchored within religious and sharaf (family honor) discourse; (2) religious validation connecting academic perseverance to spiritual purpose and family dignity; and (3) future-oriented hope linking present effort to comprehensive life goals. These mechanisms fulfill SDT’s psychological needs autonomy, competence, and relatedness through culturally specific expressions that extend SDT beyond its original Western individualistic assumptions into collectivistic, religiously grounded motivational frameworks. Implications: This research offers a theoretically rigorous, culturally responsive framework for understanding emotional support in Lebanese Islamic educational contexts, contributing to the decolonization of educational psychology and demonstrating that fundamental psychological needs can be authentically fulfilled through non-Western cultural mechanisms.